Teaching the millennial nursing student: using a" Flipping the Classroom" model - Towle, Antoinette; Breda, Karen (Nursing and Health, 2014)
Keywords: dept.nur

Essentials of nursing law and ethics - Westrick, Susan J. (Jones & Bartlett Learning, 2014)
Keywords: Law and legislation; Nursing ethics; Nursing; United States; dept.nur; faculty_collection

NLN's simulation leaders give SIRC bibliography site a Makeover - Alfes, C.M.; Aronson, B.; Bethards, M.L.; Chesney, T.; De Luna, R.; Newton, R.; Weaver, A. (Nursing Education Perspectives, 2014)
Keywords: Databases, Bibliographic; Health Information Management; Humans; Internet; Models, Educational; Patient Simulation; Societies, Nursing; United States; article; bibliographic database; dept.nur; educational model; human; medical information system; nursing organization; organization and management; peer-reviewed; teaching

The knowledge patients impart - Green, C.A. (Clinical Journal of Oncology Nursing, 2014)
Keywords: Death; Humans; Knowledge; Nurse-Patient Relations; Patients; dept.nur; human; knowledge; nurse patient relationship; patient

Self-Transcendence and Medication Adherence in Older Adults With Hypertension. - Thomas, Nezbile; Dunn, Karen (Journal of Holistic Nursing, 2014)
Purpose: The purpose of this study was to examine the relationship between self-transcendence and medication adherence among older adults prescribed antihypertensive medication., Design: Descriptive, correlational research design., Method: Forty-six older adults who were prescribed antihypertensive medications from an independent living facility participated in this study. Participants were given a survey that included a demographic questionnaire, the Morisky Medication Adherence Scale, and Reed's Self-Transcendence Scale., Findings: No significant relationship was found between medication adherence and self-transcendence (r = -.20, p = .18). Ninety percent of the participants however, admitted to cutting back or stopping their medication without notifying their providers., Conclusion: Continued investigation is needed to identify reasons why older adults fail to adhere to taking prescribed hypertension medications in order to improve health outcomes in this population., (C)2014Sage Publications
Keywords: dept.nur; hypertension older adults; medication adherence; peer-reviewed; self-transcendence

Improving sleep-wake disturbances in patients with cancer - Lamberti, Mary Patricia (Clinical Journal of Oncology Nursing, 2014)
Patients with cancer tend to suffer sleep-wake disturbances at a higher rate than the general population. Insomnia and fatigue should be regarded as a significant patient safety issue, as poor sleep can elevate patients' risks of falls, motor vehicle accidents, and acute infectious illnesses. To alleviate those risks, oncology nurses should be familiar with effective evidence-based practices for assessing and improving patients' sleep quality.
Keywords: Accidental Falls; Accidents, Traffic; Cancer; Humans; Infection; Interventions; Neoplasms; Patient Safety; Safety; Sleep; Sleep Wake Disorders; complication; dept.nur; falling; human; infection; neoplasm; patient safety; traffic accident

School nurses breaking the sounds of silence through advocacy - Resha, Cheryl; Lambert, Dawn (NASN School Nurse, 2014)
Keywords: dept.nur